Force‐sensitive afferents recruited during stance encode sensory depression in the contralateral swinging limb during locomotion. (26th March 2013) - Hochman, Shawn; Hayes, Heather Brant; Speigel, Iris; Chang, Young‐Hui
Abstract : Afferent feedback alters muscle activity during locomotion and must be tightly controlled. As primary afferent depolarization‐induced presynaptic inhibition (PAD‐PSI) regulates afferent signaling, we investigated hindlimb PAD‐PSI during locomotion in an in vitro rat spinal cord–hindlimb preparation. We compared the relation of PAD‐PSI, measured as dorsal root potentials (DRPs), to observed ipsilateral and contralateral limb endpoint forces. Afferents activated during stance‐phase force strongly and proportionately influenced DRP magnitude in the swinging limb. Responses increased with locomotor frequency. Electrical stimulation of contralateral afferents also preferentially evoked DRPs in the opposite limb during swing (flexion). Nerve lesioning, in conjunction with kinematic results, support a prominent contribution from toe Golgi tendon organ afferents. Thus, force‐dependent afferent feedback during stance binds interlimb sensorimotor state to a proportional PAD‐PSI in the swinging limb, presumably to optimize interlimb coordination. These results complement known actions of ipsilateral afferents on PAD‐PSI during locomotion.